Perancangan Dan Pengembangan Sıstem Poınt Of Sale Pada Toko Aılısa Collectıon - Suwarno Suwarno; Melvy Devalia (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
Business activities can be controlled by the rapid advancement of technology. Therefore with correct information system implementation can help business competitive. This practical project is implemented on Ailisa Collection which is a micro, small, medium enterprise which engages in women’s cosmetics and accessories. The existing problem is Ailisa Collection still use manual recording for sale and purchase transactions and no recording for inventory supply which made the owner have difficulties in finding out the profit or loss and exact amount of stock in inventory which determines decision making. The output from this job training is a web based point of sales system which will help the development of the business. The point of sales system is developed using Sublime Text 3, XAMPP, and Google Chrome with HTML, CSS, PHP as the programming language